1992
DOI: 10.1002/jcp.1041520125
|View full text |Cite
|
Sign up to set email alerts
|

Production of granulocyte colony‐stimulating factor and granulocyte/macrophage‐colony‐stimulating factor after interleukin‐1 stimulation of marrow stromal cell cultures from normal or aplastic anemia donors

Abstract: We have studied stromal cell function in naive or interleukin-1 (IL-1)-stimulated (100 pg/ml) long-term marrow cultures (LTC) from 12 normal donors and 21 patients with severe aplastic anemia (AA). Conditioned media (CM) from normal LTC contained levels of erythroid burst-promoting activity (BPA) and granulocyte/macrophage (GM) colony-stimulating activity (CSA) comparable to those previously described (Migliaccio et al., [1990] Blood, 75:305-312). The addition of IL-1 to these cultures increased the level of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Assays for inhibiting activities were negative, suggesting that the lack of CFU-GM growth was due to the absence of colony-stimulating activities. By using a sensitive nuclease protection assay we could demonstrate that AD169-infected stromal cells lack G-CSF transcripts but have unaltered levels of GM-CSF, a result in keeping with the bioassay results and the data of Migliaccio et al, which showed that CFU-GM-stimulating activity is accounted for by G-CSF whereas the burst-promoting activity is attributable to GM-CSF (29).…”
Section: Discussionsupporting
confidence: 87%
“…Assays for inhibiting activities were negative, suggesting that the lack of CFU-GM growth was due to the absence of colony-stimulating activities. By using a sensitive nuclease protection assay we could demonstrate that AD169-infected stromal cells lack G-CSF transcripts but have unaltered levels of GM-CSF, a result in keeping with the bioassay results and the data of Migliaccio et al, which showed that CFU-GM-stimulating activity is accounted for by G-CSF whereas the burst-promoting activity is attributable to GM-CSF (29).…”
Section: Discussionsupporting
confidence: 87%
“…The formation of an adherent stromal layer was reduced in the majority of aplastic samples compared to controls, which all grew to 75-100% confluence. Growth impairment ranged from massive (<5-10% of normal; patients 1-6) to moderate (25-502 of normal; patients [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Stroma confluence was comparable to normal in only one-third of AA marrows (patients 2 1-30).…”
Section: Growth Of Bone Marrow Stroma and Fibroblast Culturesmentioning
confidence: 99%
“…Several investigators have used this culture system to evaluate the func-tion of stromal cells in AA in terms of growth and hematopoietic activity. Results have shown abnormalities in function and morphology of cells in AA cultures, but the incidence of stromal defects varied widely between individual studies (8)(9)(10)(11)(12)(13)(14)(15). The role of stroma-derived growth factors in the etiology and clinical manifestation of AA remains therefore poorly understood.…”
Section: Introductionmentioning
confidence: 99%